miR-218 in adolescence predicts and mediates vulnerability to stress - Torres-Berrío, Angélica (Biol Psychiatry, 2020)
BACKGROUND: Adolescence is a period of increased vulnerability to psychiatric disorders including depression. Discovering novel biomarkers to identify individuals who are at high risk is very much needed. Our previous work shows that the microRNA miR-218 mediates susceptibility to stress and depression in adulthood, by targeting the Netrin-1 guidance cue receptor gene Dcc (Deleted in colorectal cancer) in the medial prefrontal cortex (mPFC). METHODS: Here we investigated whether miR-218 regulates Dcc expression in adolescence and could serve as an early predictor of lifetime stress vulnerability in male mice. RESULTS: miR-218 expression in the mPFC increases from early adolescence to adulthood and correlates negatively with Dcc levels. In blood, postnatal miR-218 expression parallels changes occurring in the mPFC. Notably, circulating miR-218 levels in adolescence associate with vulnerability to social defeat stress in adulthood, with high levels associated with social avoidance severity. Indeed, downregulation of miR-218 in the mPFC in adolescence promotes resilience to stress in adulthood. CONCLUSIONS: miR-218 expression in adolescence may serve both as a marker of risk and as a target for early interventions.